Export of agricultural products of Ukraine in the conditions of eurointegration: legal realities and prospects - Кульчій, Інна Миколаївна (Problems of legality, 2018)
The author researched the legal regulation of agricultural exports and analyzed national agrarian legislation and EU legislation in this area. The legal basis for regulating the export of agricultural products to the European market is a significant regulatory and legal base, consisting both of national agricultural legislation and of EU legislation. It is proposed to classify the agrarian legislation of Ukraine in this area into the general legislation and the special legislation. The author proposes to differentiate the special legislation on the subjects and on the objects of legal relations in the sphere of export of agricultural products. The author refers to the first group of legal acts that define the legal status of subjects of agrarian legal relations that can carry out activities in the export of agricultural products of Ukraine. The second group consists of those national legal acts aimed at regulating the production, processing and marketing of certain types of agricultural products: products of plant origin; products of animal origin; organic agricultural products. Legislation regulating the import of agricultural products to the EU countries is divided into: general (EU legislation regulating the EU common agricultural policy; special (EU regulations, directives, decisions, recommendations and communications, which establish requirements for the production and processing of certain types of agricultural products). The author concluded that there is no comprehensive state agricultural policy in Ukraine in the area of access to international markets and promoting the export of agricultural products. It is proposed to adopt the draft Single Integrated Strategy and Action Plan for Agricultural and Rural Development for 2015–2020, which needs to be complemented by clear measures aimed at eliminating non-tariff restrictions on exports of agricultural products to EU countries.